2005
DOI: 10.4067/s0717-95022005000200003
|View full text |Cite
|
Sign up to set email alerts
|

Efectos del Albendazol en el Hígado de Feto de Rata: Estudios Morfológico y Morfométrico

Abstract: RESUMEN:El objetivo del presente trabajo fue caracterizar morfológica, morfométrica y estereológicamente las alteraciones causadas por la administración de albendazol en ratas preñadas en el hígado de los fetos. Fueron usadas ratas Wistar, que recibieron entre los días 9 y 11 de la preñez, una dosis diaria de 5 mg/kg de peso de albendazol. Las ratas control recibieron volumen semejante de suero fisiológico en los mismos días. Al 20º día, las ratas fueron sacrificadas por inhalación de éter, siendo retirados lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…The anomalies and resorptions observed in this study when the drug was administered at day 10 of pregnancy suggest that ABZSO crosses the placental barrier in agreement with research in ovine (Cristofol et al, 1997) and rats (Capece et al, 2001). These findings are consistent with those of other studies that showed anomalies and resorptions when the drug was administered on a determined day or for a long period during gestation time (Capece et al, 2001;Teruel et al;Carrara Moreti et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…The anomalies and resorptions observed in this study when the drug was administered at day 10 of pregnancy suggest that ABZSO crosses the placental barrier in agreement with research in ovine (Cristofol et al, 1997) and rats (Capece et al, 2001). These findings are consistent with those of other studies that showed anomalies and resorptions when the drug was administered on a determined day or for a long period during gestation time (Capece et al, 2001;Teruel et al;Carrara Moreti et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…For the liver, the hepatocytes of the three zones of the hepatic accia of Rappaport were studied: periportal, intermediate and perivenous. The following histological characteristics of the liver tissue were detailed: hepatocyte (relation nucleus cytoplasm, chromatin and presence or absence of intracytoplasmic inclusions), periportal spaces and characteristics of the triad [37,38]. Finally it was evaluated in all cases presence or not of ballonizing degeneration and lipid micro-or macro-vesicles, dilatation of the centrilobular veins (qualitative observation), inflammatory infiltrate in the portal cells and increased connective tissue in the hepatic parenchyma (Masson's trichromic stain).…”
Section: Liver and Brain Histologymentioning
confidence: 99%